Identificação e genotipagem do vírus da síndrome da mancha branca (WSSV) isolado de Litopenaeus vannamei no estado do Rio Grande do Norte - Peixoto, Emanuelly Cristina Rodrigues (2016)
White spot syndrome is an acute conatgious disease whose etiologic agent is the White Spot Syndrome Virus (WSSV) responsible for serious economic losses in world acquaculture. Since 2012, it has been notified WSSV occurrence in the state of Rio Grande do Norte - RN, one of most important shrimp production region. Despite its importance, there is a lack of information about the origins and biodiversity of circulating virus. The aim of investigation was to detect WSSV in Litopenaeus vannamei from farms in the RN as well as perform genotyping of the isolates. A total of five farms were surveyed, from which 10 samples were collected each one. We selected two ponds of each of the farms, chosen because clinical suspicion of WSSV. Genomic DNA was extracted to detect the virus by polymerase chain reaction (PCR). Subsequently, was performed by PCR genotyping of the positive DNA samples analysing variable number of tandem repeats - VNTR in three molecular markers (ORFs 75, 94 and 125). The results revealed the presence of virus in only one of the 5 analyzed farms. The loci ORF 75 and ORF 94 were identified in isolates from positive farm and no amplification failure for ORF 125. The number of repeating units (RUs) was calculated, and found to 9 repetitions ORF 75 and 10 RUs to ORF 94, a pattern that had not been described, stressing the need for more strain typing for screening and surveillance of the disease